Weak gravity conjecture validation with photon spheres of quantum corrected Reissner–Nordstrom–AdS black holes in Kiselev spacetime - Mohammad Reza Alipour; Mohammad Ali S. Afshar; Saeed Noori Gashti; Jafar Sadeghi (European Physical Journal C: Particles and Fields, 2025)
Abstract In this study, we investigate the Weak Gravity Conjecture (WGC) in the context of quantum-corrected Reissner–Nordstrom–AdS (RN-AdS) black holes within Kiselev spacetime. Our focus is on photon spheres, which serve as markers for stable and unstable photon spheres. We confirm the validity of the WGC by demonstrating that quantum corrections do not alter the essential charge-to-mass ratio, thereby supporting the conjecture’s universality. Our analysis reveals that black holes with a charge greater than their mass $$(Q > M)$$ ( Q > M ) possess photon spheres or exhibit a total topological charge of the photon sphere $$(\text {PS} = -1),$$ ( PS = - 1 ) , which upholds the WGC. This finding is significant as it reinforces the conjecture’s applicability even in the presence of quantum corrections. Furthermore, we examine various parameter configurations to understand their impact on the WGC. Specifically, we find that configurations with $$ω = -\frac{1}{3}$$ ω = - 1 3 and $$ω = -1$$ ω = - 1 maintain the conjecture, indicating that these values do not disrupt the charge-to-mass ratio required by the WGC. However, for $$ω = -\frac{4}{3},$$ ω = - 4 3 , the conjecture does not hold, suggesting that this particular parameter value leads to deviations from the expected behavior. These results open new directions for research in quantum gravity, as they highlight the importance of specific parameter values in maintaining the WGC. The findings suggest that while the WGC is robust under certain conditions, there are scenarios where it may be challenged, prompting further investigation into the underlying principles of quantum gravity.